The Impact of Macroeconomic Factors on Current Account Deficit in ASEAN Countries - Ahmad, Zuriyati; Jafre, Nor Aziela; Kamarudin, Wan Norsyakila Wan (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In most ASEAN nations, a deficit in the current account balance began in 2018, sparking concerns among these countries. The deficit in the current account has led to various disadvantages in ASEAN countries, harming the nation’s economic health. Therefore, this paper analyzes the macroeconomic factors influencing the current account deficit in selected ASEAN countries. Data from eight ASEAN countries were analyzed using a panel static approach. Findings reveal that exchange rate (ER), Term of trade (TOT) and interest rate (IR) are the main factors that influence the deterioration of current account balances. Meanwhile, money supply (MS), and oil price (OILP) showed insignificant relationships towards current account balances. As ER, IR and TOT influence the current account significantly, it is suggested that the authorities in ASEAN countries have policy reforms and macroeconomic adjustments accordingly to improve the current account deterioration.